Institutional Study of the Management of Tri-City Cooperation (IKN-Samarinda-Balikpapan) and its Surrounding Areas - Ugeng Wijanarko (Journal of Social Research, 2026)
This study examines the institutional framework for managing cooperation between three cities (IKN, Samarinda, and Balikpapan) and their surrounding regions (East Kalimantan Province, North Penajam Paser Regency, and Kutai Kartanegara Regency). the research addresses critical challenges in inter-regional governance, particularly the need for coordinated metropolitan management to support IKN's vision as a global city. The objective is to identify a sustainable institutional model and the necessary regulatory mechanisms for effective collaboration that can accommodate both public service delivery and regional economic development. Utilizing a comparative analysis approach, this research examines similar cooperative models both domestically and internationally, focusing on governance structures, decision-making mechanisms, and their effectiveness in metropolitan contexts. The study employs policy review, comparative institutional analysis, contextualization through pros-cons evaluation, and focus group discussions with experts and practitioners. The findings suggest that integrating the regional management model (RM Barlingmascakeb) and the coordination board model (BKSP Jabodetabekjur) could serve as robust frameworks for collaboration, with international references from the Greater London Authority and Tokyo Metropolitan Government providing additional insights. Furthermore, the establishment of regulatory guidelines through the Head of OIKN Regulation will ensure smooth implementation and long-term success. This study provides valuable insights for local governments and the IKN authority to develop coordinated policies that foster socio-economic development while ensuring equitable growth across the regions involved. The research contributes to metropolitan governance literature by proposing context-specific institutional arrangements that address the unique dual status of OIKN as both a ministerial institution and a special regional government.